Islamic Historical Review on Middle Age Lunar Crescent Visibility Criterion - Muhamad Syazwan Faid; Mohd Nawawi, Mohd Saiful Anwar; Mohd Hafiz Mohd Saadon; Nazhatulshima Ahmad; Ali @ Mat Zin, Aizan (Journal of Al-Tamaddun, 2022)
Middle Age lunar crescent visibility criterion is criterion that was produced during 8th until 17th century. This includes al-Khawarizmi lunar crescent visibility criterion in 8th century until al-Lathiqi lunar crescent visibility criterion in 17th century. Numbers of review on mathematics and astronomy during the Middle Age, however the number of review that specifically written for Middle Age lunar crescent visibility criterion limited, with majority of review is written to study the historical of Middle Age science, astronomy, mathematics and geography as a whole, and not converge on lunar crescent visibility criterion. . Therefore, this article aimed to provide a review on Middle Age lunar crescent visibility criterion. The review is conducted using literature analysis, snowball literature search and specific inclusion and exclusion criteria. The review is performed based on 13 works on lunar crescent visibility criterion that pass the selection criteria. The review found out that most of the lunar crescent visibility criterion is based on al-Khawarizmi arc of separation and solar longitude, lunar crescent visibility criterion, with exception on Ibn Tariq, Ibn Qurra and Ibnu Yunus lunar crescent visibility criterion that adopt angular distance or elongation. The review suggest that a new outlook on Middle Age lunar crescent visibility criterion study can be done, by conducting an assessment on new data of moonsighting, and comparing with modern lunar crescent visibility criterion research.